Money talks : beyond the piggy bank - Musta’ein, Asyiqin (Nanyang Technological University, 2021)
Money Talks, a childhood financial education campaign, was launched in January 2021 to inspire Singaporean parents with children aged 6 to 12 years to make frequent money conversations a part of family life. In less than 3 months, the campaign successfully earned a positive achievement index for all fourteen output objectives, and increased parents’ intentions to engage in financial education with their child(ren) at least once a week by 15.87%, as well as their actual behaviours by 10.10%. This paper explores the underestimated role that parents play in shaping a child’s relationship with money, and presents our attempt to reverse the current trend where children’s financial education is often placed on the backburner. Our literature review and primary research identified notable challenges and societal factors, such as difficulties locating childhood financial education resources, that contribute to a lack of depth and consistency in the way parents cultivated their child’s financial literacy from young. Guided by the Integrated Model of Behavioural Prediction (IMBP), capitalising on perceived norms and framing the task of conducting financial education as an easily achievable one with lifelong benefits were critical in driving the campaign’s key messaging online and offline. To sustain parents’ interest over the length of the campaign, we adopted an empowering tone-of-voice and chose to ground all initiatives on the pillars of Save, Spend and Share. This included the production of our Money Talks Kit, a ready-to-use resource launched just ahead of our month-long #OurMoneyTalks social media contest to provide families with an easy guide to weekly money conversations at home. The campaign also partnered with experts for our Money-smart Parenting webinar and a six-episode Hear from Experts video series, both of which offered parents insights and solutions to navigate the issues influencing children as young consumers today.